Understanding the use of superstitious rituals in sports people - Morris, B.; Thornton, C.; Neave, N.; Allen, G. (Journal of Sports Sciences, 2025)
Superstitious Rituals (SRs) are actions which individuals believe to be powerful in controlling luck or external variables. SRs are commonplace in sporting environments, whereby the difference between success and failure can be attributed to the smallest variable. It is therefore important to understand how athletes use SRs and how they, in turn, influence the athlete. This study explored the experiences of athletes to better understand how they both view and experience SRs. Sixteen individual semi-structured interviews and five focus groups were conducted with 30 participants. Three themes were identified during the thematic analysis process: Identifying Superstitions and Their Uses; The Lifecycle of Superstitious Rituals; and Sporting Classifications & The Influence of Competitive Prestige. The results demonstrate the physical and mental impacts, including confidence and anxiety, that SRs have on athletes and how SRs differ in their timings and intent. Additionally, athletes who formed SRs via operant conditioning tended to discard them when unrewarded, while those adopting SRs from others often maintained them despite lack of reinforcement.